An epidermal growth factor receptor variant III–targeted vaccine is safe and immunogenic in patients with glioblastoma multiforme - Sampson, John H. (2009)
Conventional therapies for glioblastoma multiforme (GBM) fail to target tumor cells exclusively, such that their efficacyis ultimately limited by nonspecific toxicity. Immunologic targeting of tumor-specific gene mutations, however, may allow more precise eradication of neoplastic cells. The epidermal growth factor receptor variant III (EGFRvIII) is a consistent and tumor-specific mutation widely expressed in GBMs and other neoplasms. The safety and immunogenicity of a dendritic cell (DC)–based vaccine targeting the EGFRvIII antigen was evaluated in this study. Adults with newly diagnosed GBM, who had undergone gross-total resection and standard conformal external beam radiotherapy, received three consecutive intradermal vaccinations with autologous mature DCs pulsed with an EGFRvIII-specific peptide conjugated to keyhole limpet hemocyanin. The dose of DCs was escalated in cohorts of three patients. Patients were monitored for toxicity, immune response, radiographic and clinical progression, and death. No allergic reactions or serious adverse events were seen. Adverse events were limited to grade 2 toxicities. The maximum feasible dose of antigen-pulsed mature DCs was reached at 5.7 × 10(7) ± 2.9 × 10(7) SD without dose-limiting toxicity. EGFRvIII-specific immune responses were evident in most patients. The mean time from histologic diagnosis to vaccination was 3.6 ± 0.6 SD months. Median time to progression from vaccination was 6.8 months [95% confidence interval (C.I.(95)), 2.5–8.8], and median survival time from vaccination was 18.7 months (C.I.(95), 14.5–25.6). Overall median survival from time of histologic diagnosis was 22.8 months (C.I.(95), 17.5–29). This study establishes the EGFRvIII mutation as a safe and immunogenic tumor-specific target for immunotherapy.